2000
DOI: 10.1088/0953-8984/12/28/306
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor-metal transition in liquid As-Te mixtures

Abstract: EXAFS, conductivity and Hall coefficient measurements have been carried out for liquid As-Te mixtures. EXAFS analysis reveals the presence of chemical disorder marked by the existence of homopolar As-As and Te-Te pairs. At high temperature around 500 • C the network structure composed of threefold coordinated As atoms and twofold coordinated Te atoms is transformed into the twofold chain structure. The network-chain transformation is accompanied by the gradual semiconductor to metal transition which is demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
5
20
0
Order By: Relevance
“…Of particular interest are the As x Te 100−x glasses that serve as model systems, but an atomistic understanding of the structure−property relations in it remains obscure due to controversies [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The As 2 Te 3 melt, similar to the Te melt, is a metal at small overheating above the melting temperature [16,17], as a result, cooling-induced crystallization can be avoided only at quenching rates above 100 K/s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest are the As x Te 100−x glasses that serve as model systems, but an atomistic understanding of the structure−property relations in it remains obscure due to controversies [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The As 2 Te 3 melt, similar to the Te melt, is a metal at small overheating above the melting temperature [16,17], as a result, cooling-induced crystallization can be avoided only at quenching rates above 100 K/s.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was established more recently that stoichiometric glassy g-As 2 Te 3 strongly differs in structure of the short-range order from the crystalline phase and is characterized by a chemical disorder of 30 to 60% (chemical disorder is defined as the number of homopolar As-As bonds to the total number of As-Te and As-As bonds) [3][4][5][6][7][8][9][10][11][12]. Furthermore, the analysis of the structure of g-As 2 Te 3 is also complicated because of a strong dependence on the fabrication procedure [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…The As-Te glasses have been studied for various applications based on their promising properties [1][2][3][4][5][6]. The effect of thermal annealing on the optical properties of chalcogenide glasses has been studied and interpreted according to the density of states model in amorphous materials proposed by Mott et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, measurements of the electrical conductivity, Hall coefficient and thermoelectric power for liquid As-Te mixtures at different temperatures demonstrate that the liquid mixtures undergo a semiconductor to metal (S-M) transition. The transition temperature moves toward higher temperature with increasing As concentration, which is slightly different from that of networkchain transformation [7,8]. These findings enrich and illuminate the phenomenology of As chalcogenides in the liquid state.…”
Section: Introductionmentioning
confidence: 77%
“…For liquid As 40 Te 60 , an exothermic peak appears at 780 K in the differential scanning calorimetric (DSC) curves under cooling, while the density shows a maximum around the corresponding temperature, indicating that a somewhat structural change occurs [6]. The experimental results from extended X-ray absorption fine structure (EXAFS) studies also suggested that there is a structural transformation above 500°C from the network structure composed of threefold coordinated As atoms and twofold coordinated Te atoms to the chain structure [7]. Moreover, measurements of the electrical conductivity, Hall coefficient and thermoelectric power for liquid As-Te mixtures at different temperatures demonstrate that the liquid mixtures undergo a semiconductor to metal (S-M) transition.…”
Section: Introductionmentioning
confidence: 99%